Truncated hexagonal bi-pyramidal gallium ferrite nanocrystals: integration of structural details with visible-light photo-activity and self-cleaning properties. Issue 27 (7th June 2018) - Mishra, Monali; Mukherjee, Indrani; Mall, Ashish Kumar; Mitra, Arijit; Dash, Sukalyan; Chatterjee, Sriparna; Mukherjee, Somdutta; Roy, Amritendu
Abstract : THBP-GFO nanocrystals with novel structural symmetry demonstrate impressive self-cleaning property. Abstract : We report the growth of gallium ferrite (GaFeO3 or GFO) nanocrystals with a unique morphology, "truncated hexagonal bi-pyramid" (THBP), and with a novel orthorhombic P 21 21 21 symmetry under hydrothermal conditions in pure water without using any reducing or shape defining reagent. The growth conditions of such a structure are optimized through a detailed study using field emission scanning electron microscopy. The structural details of the above hitherto unreported phase of the material are studied using room temperature powder X-ray diffraction (XRD), Raman spectroscopy, high resolution transmission electron microscopy and ab initio electronic structure calculations. In light of the above structural characterization, a possible mechanism for the formation of the specific shape of hexagonal bi-pyramid is proposed. Our investigations on optical, photocatalytical and wetting characteristics of the as-grown nanocrystals demonstrate their visible light photocatalytic activity as well as a strong-hydrophilic character. The material is poised to establish itself as a new "self-cleaning" material.